2006
DOI: 10.1007/s00384-006-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

Rare tumors of the colon and rectum: a national review

Abstract: This study provides the first population-based analysis of the epidemiology, tumor characteristics, and survival rates for rare CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 20 publications
6
94
1
3
Order By: Relevance
“…We also confirmed previous observations that tumor size and muscle layer invasion are important predictive criteria in assessing the malignant nature of rectal carcinoids 1,2,[14][15][16][17][18][19]23,28,33,34 and that patients with typical and atypical bronchopulmonary carcinoid tumors display significantly different metastatic possibilities and 10-year postoperative survival rates. [35][36][37][38] In addition, we demonstrated that thymic carcinoids, also known as welldifferentiated neuroendocrine carcinomas, usually bear high risks for recurrence, metastasis, and tumor-associated death, and patients with thymic carcinoids have a worse prognosis compared with bronchial carcinoids.…”
Section: Metastases and Survivalsupporting
confidence: 90%
See 1 more Smart Citation
“…We also confirmed previous observations that tumor size and muscle layer invasion are important predictive criteria in assessing the malignant nature of rectal carcinoids 1,2,[14][15][16][17][18][19]23,28,33,34 and that patients with typical and atypical bronchopulmonary carcinoid tumors display significantly different metastatic possibilities and 10-year postoperative survival rates. [35][36][37][38] In addition, we demonstrated that thymic carcinoids, also known as welldifferentiated neuroendocrine carcinomas, usually bear high risks for recurrence, metastasis, and tumor-associated death, and patients with thymic carcinoids have a worse prognosis compared with bronchial carcinoids.…”
Section: Metastases and Survivalsupporting
confidence: 90%
“…They are derived from the enterochromaffin/neuroendocrine cell compartments, which usually are scattered throughout the body. [1][2][3][4][5][6][7] Carcinoid tumors represents approximately 0.49% of all malignancies, and the incidence is estimated from 0.65 to 4.48 per 100,000 population per year. [7][8][9][10][11][12] The gastrointestinal tract and respiratory system usually are the most common sites for carcinoid tumors, reflecting the high density of enterochromaffin/neuroendocrine cells in the mucosa of the digestive system and the respiratory epithelium.…”
mentioning
confidence: 99%
“…Similar results in a Tunisian study where CRC adenocarcinoma was well differentiated in 46% of cases, moderately differentiated in 33.3% of cases and undifferentiated in 11.3% of cases [55]. Our series and the Moroccan series report the same results [47,56,57].…”
Section: Discussion:-supporting
confidence: 91%
“…From a review of the population study, the overall 5-year survival for rectal SCC was found to be 48.9% compared with 62.1% for adenocarcinoma. When localised, the 5 years OS was 73.7% versus 91.8% for adenocarcinoma, with 31.3% versus 65.8% for regional and 20.8% versus 8.8% for metastatic disease (17) .…”
Section: Discussionmentioning
confidence: 94%